Developing Audio Media on Listening Skill Using Microsoft Sways and T2S Application for Junior High School - Ziyad Muhamad Iqbal; Ahmad Saifudin; Widiarini Widiarini; Siti Rofi’ah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Considering the limitation of use learning media in English subjects in junior high school the use of learning media to hone listening skills has never been given to students. Even though audio media is needed to make easy for teacher to hone the student listening skill and to make easy for student to understand English pronunciation and conversation. Therefore, researchers developed Audio Media in English Subjects for 7th grade. This study aims to develop learning media in the form of Audio or Mp3 and see how the feasibility of the media in order to produce valid, effective and responsive media. The data research survey was to use observation, unstructured interviewed and questionnaire for research and development of Audio Media which was suitable to use by media experts, material experts, English teachers and student responses. This research uses Research and Development methods. The development procedure follows the Borg and Gall in Sugiyono (2015) procedure carried out by involving the ten main steps however this research is simply to use six stages. The results of this research found that media audio have good feasibility according to media experts get a proportion of 82%, material experts 82%, teachers’ assessment 77% and students’ responses 71% which means that this Learning Media is